2016
DOI: 10.1002/ejoc.201600038
|View full text |Cite
|
Sign up to set email alerts
|

CuI‐Catalyzed Synthesis of Propargyl Hydroperoxides Using Molec­ular Oxygen and Hydroxylamines

Abstract: A CuI‐catalyzed oxidation of enynes using N‐hydroxybenzotriazole (HOBt) or N‐hydroxyphthalimide (NHPI) with molecular oxygen has been developed to yield propargyl hydroperoxides. The reaction occurs under O2 at 0 °C to afford hydroperoxides in 1–4 h. This method provides an alternative to H2O2 or tBuOOH by using molecular oxygen as the source of oxygen atoms. The resulting hydroperoxides can be protected prior to purification and converted into alkoxyamines upon treatment with hydrazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 45 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…A Cu I -catalyzed oxidation of enynes using N-hydroxybenzotriazole (HOBt) or Nhydroxyphthalimide (NHPI) with molecular oxygen has been developed to yield propargyl hydroperoxides [21]. The reaction occurs under O 2 at 0°C to afford hydroperoxides in 1-4 h. This method provides an alternative to H 2 O 2 or tBuOOH by using molecular oxygen as the source of oxygen atoms.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…A Cu I -catalyzed oxidation of enynes using N-hydroxybenzotriazole (HOBt) or Nhydroxyphthalimide (NHPI) with molecular oxygen has been developed to yield propargyl hydroperoxides [21]. The reaction occurs under O 2 at 0°C to afford hydroperoxides in 1-4 h. This method provides an alternative to H 2 O 2 or tBuOOH by using molecular oxygen as the source of oxygen atoms.…”
Section: Synthesismentioning
confidence: 99%
“…The reaction occurs under O 2 at 0°C to afford hydroperoxides in 1-4 h. This method provides an alternative to H 2 O 2 or tBuOOH by using molecular oxygen as the source of oxygen atoms. The resulting hydroperoxides can be protected prior to purification and converted into alkoxyamines upon treatment with hydrazine [21]. Jiang et al, observed that SnCl 4 •5H 2 O and SnCl 2 •2H 2 O were efficient catalysts for the oxidation of acetone with 30% hydrogen peroxide at room temperature.…”
Section: Synthesismentioning
confidence: 99%
“…Recently, Miner and Woerpel successfully utilized HOBt and molecular oxygen as a source of oxygen atoms for the copper‐catalyzed radical dioxygenation of enynes (Scheme ). In the case of a cyclic enyne 65 as substrate the trans ‐dioxygenated product 66 was obtained in a high diastereomeric ratio …”
Section: Anti‐dioxygenation By Radical Pathwaysmentioning
confidence: 99%
“…Woerpel and co-workers reported copper(I)-catalyzed hydroperoxidation of 1,3-enynes with molecular oxygen in the presence of NHPI and HOBt at 0°C in MeCN (Scheme 22). [23] The ene components were selectively oxidized, resulting in the accumulation of propargyl hydroperoxides in high yields. The reaction of a cyclic enyne was also performed smoothly to afford the product as a mixture of diastereomers.…”
Section: Intermolecular Dioxygenationsmentioning
confidence: 99%